Digital financial inclusion and tax policies - (:unkn) unknown (My University, 2022)
In developing countries, financial inclusion is a real challenge, as it would help achieve some of the Sustainable Development Goals (SDGs), in particular the reduction of poverty or income and gender inequalities. With the rise of digital technology, access to broadband connections and the democratization of cell phones, financial services such as "Mobile Money" have emerged. This digital financial service is presented as a way to quickly and completely achieve the goal of financial inclusion in developing countries. The main providers of this financial service in developing countries are mobile network operators, which are fiscally considered to be part of a high value-added sector. Thus, the objective of this paper is to make a significant contribution to the existing literature on digital financial inclusion in developing countries, particularly African countries. The first part, consisting of chapters 2 and 3, examines the impact of mobile money accessibility and availability on economic policy objectives. The second part, also consisting of two chapters (chapter 4 and 5), analyzes the impact of taxation on the use of digital financial services. Chapter 2 focuses on the relationship between economic growth and financial inclusion in developing countries. The originality of the analysis is to report on the contribution of mobile money to economic growth. Based on a panel of 57 developing countries for a period from 2007 to 2017, the analysis suggests a positive impact of financial inclusion on growth. It also reveals that the contribution to growth of digital financial inclusion via mobile money is greater than that of formal inclusion with commercial banks in developing countries. Chapter 3 looks at Mobile Money as a determinant of business creation in Africa. The question is whether the availability of Mobile Money on the continent has enabled people to provide themselves with income and livelihood through entrepreneurship. The chapter finds that
Keywords: African Research